2017
DOI: 10.17116/jnevro2017117714-9
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of leukocyte count in the venous blood in the acute stage of cerebral aneurism rupture

Abstract: The increase in leukocyte number in the venous blood in the first 72 h after CA rupture ≥10,1·109/L is a reliable risk factor of marked vessel spasm. The level of leukocytes in patients with cerebral ischemia and poor prognosis in the first 72h after aneurysmal hemorrhage was higher by 2-28% compared to survivors without neurological impairment or mild neurological deficit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
2
0
0
Order By: Relevance
“… Zumofen et al (2018) found in their cohort that the older was a patient, the lower was his pre-ictal functional status, and the more likely he presented in poor condition following aSAH. In recent decades, the systemic inflammatory response has attracted the clinician’s attention for assessing aSAH severity and predicting the prognosis ( Kalinkin et al, 2017 ; Gusdon et al, 2021 ; Ma et al, 2021 ); our study confirmed that the risk of developing unfavorable outcome is greater in patients with higher WBC at the time of admission. Compared with other research which revealed the prognostic value of the NLR and SIRI in patients with aneurismal subarachnoid hemorrhage ( Kalinkin et al, 2017 ; Zhang et al, 2020 ; Hu et al, 2021 ), the WBC on admission is more intuitive and accessible.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“… Zumofen et al (2018) found in their cohort that the older was a patient, the lower was his pre-ictal functional status, and the more likely he presented in poor condition following aSAH. In recent decades, the systemic inflammatory response has attracted the clinician’s attention for assessing aSAH severity and predicting the prognosis ( Kalinkin et al, 2017 ; Gusdon et al, 2021 ; Ma et al, 2021 ); our study confirmed that the risk of developing unfavorable outcome is greater in patients with higher WBC at the time of admission. Compared with other research which revealed the prognostic value of the NLR and SIRI in patients with aneurismal subarachnoid hemorrhage ( Kalinkin et al, 2017 ; Zhang et al, 2020 ; Hu et al, 2021 ), the WBC on admission is more intuitive and accessible.…”
Section: Discussionsupporting
confidence: 78%
“…In recent decades, the systemic inflammatory response has attracted the clinician’s attention for assessing aSAH severity and predicting the prognosis ( Kalinkin et al, 2017 ; Gusdon et al, 2021 ; Ma et al, 2021 ); our study confirmed that the risk of developing unfavorable outcome is greater in patients with higher WBC at the time of admission. Compared with other research which revealed the prognostic value of the NLR and SIRI in patients with aneurismal subarachnoid hemorrhage ( Kalinkin et al, 2017 ; Zhang et al, 2020 ; Hu et al, 2021 ), the WBC on admission is more intuitive and accessible. Finally, using a ventilator after endovascular coiling is included in the nomogram for elderly patients with aSAH.…”
Section: Discussionsupporting
confidence: 78%